2022
DOI: 10.33546/bnj.2024
|View full text |Cite
|
Sign up to set email alerts
|

“I can live a normal life”: Exploring adherence to antiretroviral therapy in Indonesian adolescents living with HIV

Abstract: Background: Adherence to antiretroviral therapy (ART) can be challenging since it needs to be continued for a lifetime. At their age, adolescents start to be responsible for their life, and this continued therapy might be a challenge for them. Objective: This study explored the experiences of adherence to ART in adolescents living with HIV in Jakarta, Indonesia. Methods: A qualitative study with an Appreciative Inquiry (AI) approach was employed to explore challenges adolescents face in ART adherence which foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…That HIV stigma is a major impediment to ART adherence is well established in the literature [ 9 , 13 , 39 ], as is the fact that HIV stigma in health care is highly prevalent and highly detrimental for PLHIV [ 40 , 41 , 42 , 43 ]. As such, our findings dovetail with previous studies reporting that stigma in any form hinders treatment adherence [ 3 , 11 , 27 , 30 , 31 , 32 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. PLHIV also often experience intersectional stigma or stigmatization due to multiple identities within marginalized groups (e.g., gender or sexual orientation) [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…That HIV stigma is a major impediment to ART adherence is well established in the literature [ 9 , 13 , 39 ], as is the fact that HIV stigma in health care is highly prevalent and highly detrimental for PLHIV [ 40 , 41 , 42 , 43 ]. As such, our findings dovetail with previous studies reporting that stigma in any form hinders treatment adherence [ 3 , 11 , 27 , 30 , 31 , 32 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. PLHIV also often experience intersectional stigma or stigmatization due to multiple identities within marginalized groups (e.g., gender or sexual orientation) [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies conducted in Indonesia have identified facilitators for ART adherence, including self-efficacy, knowledge, social support, and motivation ( Nuraidah et al, 2022 ; Umar et al, 2019 ; Yona et al, 2023 ). Theoretical research has predominantly focused on intentional non-adherence as a barrier to ART adherence, but unintentional non-adherence also contributes significantly to the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical research has predominantly focused on intentional non-adherence as a barrier to ART adherence, but unintentional non-adherence also contributes significantly to the problem. Barriers reported in prior studies in Indonesia encompass forgetfulness, busyness, being asleep at medication time, running out of medication, medication availability far from home, boredom, adverse effects of ART, drug size, administration problems, depression, and stigma ( Nuraidah et al, 2022 ; Nurfalah et al, 2019 ; Suryana et al, 2019 ; Umar et al, 2019 ; Weaver et al, 2014 ; Yona et al, 2023 ). Resilience engineering offers a novel perspective on adherence, focusing on the positive aspects of resilient systems.…”
Section: Introductionmentioning
confidence: 99%
“…Religious beliefs have been highlighted to play a significant role as supportive factors towards ART adherence (Fongkaew et al, 2014 ; Kisenyi et al, 2013 ) or as risk factors (Tocco, 2017 ). To date, a limited number of research studies have revealed that regular adherence to religious prayer was found to be significantly associated with high ART adherence among Muslim patients (Mbuagbaw et al, 2012 ; Nuraidah et al, 2022 ). In addition, Islamic tenets have been documented to affect ART compliance, particularly during the holy month of Ramadan (Tocco, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Islamic tenets have been documented to affect ART compliance, particularly during the holy month of Ramadan (Tocco, 2017 ). To date, scarce research explores how Islamic religious belief systems may be utilized for ART adherence among Muslim patients in the community in their everyday lives (Fongkaew et al, 2014 ; Mbuagbaw et al, 2012 ; Nuraidah et al, 2022 ). Up until the present, the experiences of Muslim patients and their religious beliefs regarding ART adherence have been scarcely explored (Fongkaew et al, 2014 ; Mbuagbaw et al, 2012 ; Nuraidah et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%